Pemberdayaan Ekonomi Masyarakat melalui Pengolahan Singkong sebagai Bahan Makanan di Desa Sekidang Kecamatan Sambeng Kabupaten Lamongan - Hadi Ismanto; Wildan Syihabuddin; Alvita Nur Aini; Bagus Eko Setiawan (Santri: Journal of Student Engagement, 2023)
The development of technology and information that is increasingly advanced at this time is still not fully understood by the community, especially among rural communities. This is indicated by the lack of community creativity in the abundance of cassava food products, where they do not realize the potential that can be created from these food products. Cassava food products are generally food products that are only processed into monotonous products such as tape, jemblem, opaque cassava, and fried cassava. So that people feel bored with the monotonous variety of processed cassava, but on the contrary if it is processed into a variety of processed cassava properly, it will have a positive impact on products that have high selling power. The expected goal of this service activity is to educate the community by making local potentials that have not been explored can be optimized, especially those that can have an impact on improving the welfare of farmers and farm workers. The implementation method is by identifying potentials and problems, planning training, socializing training, and implementing training. This activity was attended by PKK women and housewives from Sekidang Village, Sambeng District, Lamongan Regency. The results of this activity are increasing creativity and new innovations to the community, also making people aware that we can process staple foods that have high economic value and in the end can help the economy and improve the quality of life of rural communities